The Constitution - Quiri, Patricia Ryon (New York Children's Press, 1998)
Explains why a constitution was needed; describes the convention in Philadelphia in 1787, the Virginia and New Jersey plans, the Great Compromise, and the ratification process
American Corner
Includes bibliographical references (p. 44-45) and index
11
Keywords: United States -- Juvenile literature; United States; United States -- Politics and government -- 1783-1789 -- Juvenile literature; United States -- Politics and government -- 1783-1789